2021
DOI: 10.2340/00015555-3914
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Skin Symptoms after Diagnosis and on a Long-term Gluten-free Diet in Dermatitis Herpetiformis

Abstract: Dermatitis herpetiformis is a cutaneous manifestation of coeliac disease treated with a gluten-free diet. However, the itching and blistering rash alleviates slowly after gluten withdrawal and occasionally persists despite a long-term gluten-free diet. This study investigated the prevalence and factors associated with prolonged (i.e. > 2 years) and ongoing skin symptoms in 237 patients with dermatitis herpetiformis. Data were gathered from medical records and via questionnaires. Among patients with dermatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Our previous study including 78 long-term treated patients with DH showed that female patients experience more severe gastrointestinal symptoms and have decreased vitality compared with males (20). Conversely, our recent study did not detect a sex association in the presence of persistent skin symptoms (8), and studies concerning sex differences in the GFD adherence of patients with DH are lacking. Therefore, the aim of this study was to investigate the associations between sex, clinical symptoms, treatment compliance and burden of disease in long-term treated patients with DH.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Our previous study including 78 long-term treated patients with DH showed that female patients experience more severe gastrointestinal symptoms and have decreased vitality compared with males (20). Conversely, our recent study did not detect a sex association in the presence of persistent skin symptoms (8), and studies concerning sex differences in the GFD adherence of patients with DH are lacking. Therefore, the aim of this study was to investigate the associations between sex, clinical symptoms, treatment compliance and burden of disease in long-term treated patients with DH.…”
mentioning
confidence: 64%
“…A gluten-free diet (GFD) leads to recovery of the enteropathy, resolution of the skin and possible gastrointestinal symptoms, and reduction in the risk of DH complications, such as the development of lymphoma ( 1 , 7 ). Because skin symptoms alleviate slowly with GFD treatment, dapsone medication is initiated for the majority of patients after diagnosis of DH ( 1 , 8 ). Dapsone is highly effective towards skin symptoms, but does not affect the enteropathy or prevent DH-related complications, and thus strict adherence to a GFD is vital ( 1 ).…”
mentioning
confidence: 99%
“…The majority of DH patients suffer severe itching, difficulties sleeping, and even gastrointestinal symptoms. [12,14] DH is a chronic, relapsing disease that can last someone's whole life. However, DH patients who commit strictly to the GFD have a very good prognosis.…”
Section: 3 Treatment Of Dermatitis Herpetiformismentioning
confidence: 99%